Restitution of the NHS breast reconstruction service during the recovery phase of the Covid 19 pandemic. Issue 3 (March 2021) - Vigneswaran, P.; Clancy, R.; Jackson, P.C.; Wilson, S.M.; Patel, N.
Summary: During the recovery restitution phase of the coronavirus pandemic, breast reconstruction teams have faced particular challenges to restarting this essential service. This is due to the length and complexity of the surgery, along with the demands on healthcare staff. The Royal College of Surgeons have classified immediate breast reconstruction as priority 2 and the National Institute for Health and Care Excellence have provided a pre-operative pathway for resumption of elective procedures. We therefore describe our experience in restarting our service for providing a breast reconstruction service from the 29th June 2020.